2002
DOI: 10.1021/ol0258381
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of N-p-Toluenesulfinamides

Abstract: [reaction: see text] Contrasting and interesting electrochemical behavior is observed in anodic oxidation of N-substituted p-toluenesulfinamides under controlled current conditions. For sulfinamides derived from secondary alkylamines and primary arylamines, the N-sulfinyl group is removed and the corresponding amines are formed; for sulfinamides derived from primary alkylamines, sulfur oxidation yields the corresponding sulfonamides in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The enantiomeric purity of each diastereoisomer was checked by chiral HPLC and no racemization was observed. The formation of methylsulfinate 11a corresponding to the N-S bond cleavage reported by DÕOca et al 19 (Scheme 2) could not be completely avoided. Under more basic conditions, the formation of 11a was minimized and 8a was formed in a nice 77% yield but each diastereoisomer of 8a was proved to be only 80% ee.…”
Section: Tetrahedron Lettersmentioning
confidence: 93%
See 1 more Smart Citation
“…The enantiomeric purity of each diastereoisomer was checked by chiral HPLC and no racemization was observed. The formation of methylsulfinate 11a corresponding to the N-S bond cleavage reported by DÕOca et al 19 (Scheme 2) could not be completely avoided. Under more basic conditions, the formation of 11a was minimized and 8a was formed in a nice 77% yield but each diastereoisomer of 8a was proved to be only 80% ee.…”
Section: Tetrahedron Lettersmentioning
confidence: 93%
“…17 The oxidation step was particularly challenging and hypothetic since both nitrogen and sulfur atoms can be oxidized. Indeed, the anodic oxidation of sulfinylamines was reported by DÕOca et al 19 to give sulfur oxidation or N-S bond cleavage. 20 However, fragmentary data from the literature suggested that the regioselective nitrogen oxidation is possible.…”
Section: Tetrahedron Lettersmentioning
confidence: 93%
“…As a further demonstration of the utility of this method, we considered functionalizing amino acids, which would allow the preparation of nonproteinogenic building blocks for the discovery of new therapeutic peptides. The preparation of a diverse set of sulfonamides derived from glycine (26), proline (27), phenylalanine (28), serine (29) and tyrosine (30) was successful and further demonstrates the functional group tolerance of this electrochemical method. Notably, no racemization of the chiral centra was observed under these reaction conditions (see Supporting Information).…”
mentioning
confidence: 84%
“…Interestingly, no Shono-type oxidation of the amines was observed under these reaction conditions . Next, two consecutive oxidation steps of the sulfenamide take place and the targeted sulfonamide is formed via a sulfinamide intermediate . Indeed, we were able to isolate the sulfenamide intermediate and, by subjecting this compound to our reaction protocol, the corresponding sulfonamide was generated effectively (Figure C).…”
mentioning
confidence: 99%